Report of the Working Group on Fisheries for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The fisheries sector has been recognised as a powerful income and employment generator as it stimulates growth of a number of subsidiary industries and is a source of cheap and nutritious food, at the same time it is an instrument of livelihood for a large section of economically backward population of the country. More than 6 million fishers in the country depend on fisheries and aquaculture for their livelihood.
Government of India, Planning Commission